2015
DOI: 10.1177/1948550615590449
|View full text |Cite
|
Sign up to set email alerts
|

Communicating With Distant Others

Abstract: We introduce the construct of relational scope to refer to the degree to which an individual engages in communication with a more or less distant audience, with a contractive relational scope indicating a near audience and an expansive relational scope indicating a distant audience. Drawing on construal level theory, we argue that speakers use abstract messages strategically when faced with an expansive relational scope in order to be widely relevant and relatable. We show that speakers communicate more abstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(17 citation statements)
references
References 18 publications
3
10
0
Order By: Relevance
“…The current findings also contribute to prior research that explores the relationship between audience and communication abstraction (e.g., Amit, Wakslak, & Trope, 2013; Baskin et al, 2014; Joshi & Wakslak, 2014; Joshi et al, 2016). For example, previous research has found that speakers use abstract messages when addressing larger audiences (Joshi & Wakslak, 2014) and distant audiences (Joshi et al, 2016). Whereas these studies paid more attention to how the attributes of an audience shape the abstraction of the speakers’ messages, the current research examines a more extreme example of audience characteristics.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The current findings also contribute to prior research that explores the relationship between audience and communication abstraction (e.g., Amit, Wakslak, & Trope, 2013; Baskin et al, 2014; Joshi & Wakslak, 2014; Joshi et al, 2016). For example, previous research has found that speakers use abstract messages when addressing larger audiences (Joshi & Wakslak, 2014) and distant audiences (Joshi et al, 2016). Whereas these studies paid more attention to how the attributes of an audience shape the abstraction of the speakers’ messages, the current research examines a more extreme example of audience characteristics.…”
Section: Discussionsupporting
confidence: 62%
“…In this study, four conditions—(a) private, (b) private but adopting the perspectives of others, (c) observed, and (d) observed but focusing on one’s own perspective—were manipulated by instructions, and construal level was measured by asking the participants to select arguments supporting recycling. Half of the arguments related to why one should recycle, representing the superordinate and high-level feature, whereas the other half related to how recycling is done, representing the conceptualization and low-level feature (Joshi & Wakslak, 2014; Joshi et al, 2016). According to CLT, arguments focusing on why an action should be performed emphasize the superordinate and high-level features of an action, whereas arguments focusing on how an action is done emphasize the conceptualization and low-level features of an option (Liberman & Trope, 1998; Trope & Liberman, 2010).…”
Section: Studymentioning
confidence: 99%
“…Second, the study focused on the context of sending arguments to an abstract group of “smokers” instead of smokers or a smoker that participants personally know. Since audience considerations may also influence participants’ choice of arguments (Joshi & Wakslak, 2014; Joshi, Wakslak, Raj, & Trope, 2016), future studies could vary the audience type and examine the interactive effect of audience type and message exposure on replication and extension. For example, future research could examine whether the audience’s readiness to quit smoking or audience closeness (e.g., close smoker friend vs. anonymous smoker) could moderate the effects of message exposure on replication and extension.…”
Section: Discussionmentioning
confidence: 99%
“…Another approach to managing communication with socially distant close others via construal levels involves how we construct the messages and the media through which they are transmitted. For example, researchers have found that when communicating messages to psychologically distant others, we prefer to craft those messages with more abstract (vs. concrete) elements (Joshi et al., 2015). This can take many forms.…”
Section: Construal Levels and Socially Distanced Interactionsmentioning
confidence: 99%